2022
DOI: 10.1155/2022/3081380
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Effect of Minimally Invasive Percutaneous Pedicle Screw Internal Fixation Combined with Injured Vertebrae Bone Grafting in the Treatment of Thoracolumbar Fractures in Orthopedic Surgery

Abstract: Objective. To observe the clinical effect of minimally invasive percutaneous pedicle screw internal fixation combined with injured vertebrae bone grafting in the treatment of thoracolumbar fractures in orthopedic surgery. Methods. A total of 132 patients with thoracolumbar fractures admitted to the hospital were enrolled between January 2020 and April 2021. Both groups underwent minimally invasive percutaneous pedicle screw internal fixation. According to the presence or absence of intraoperative injured verte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The empty shell of the vertebral body will lead to the increase of the gap of the anterior column, the reduction of the load-bearing capacity, and the transfer of stress to the posterior fixation system, leading to the fracture or loosening of the internal fixation system. 18 The results of this study showed that the incidence of empty shell signs in the study group was lower than that in the control group during follow-up (all ps < 0.05). This may be because the upper and lower vertebral body placement of fixed screws can reconstruct the height of the cone, consolidate the correction effect of internal fixation, and then reduce the occurrence of adverse reactions such as fracture and fall off of internal fixation.…”
Section: Recovery Timementioning
confidence: 56%
See 2 more Smart Citations
“…The empty shell of the vertebral body will lead to the increase of the gap of the anterior column, the reduction of the load-bearing capacity, and the transfer of stress to the posterior fixation system, leading to the fracture or loosening of the internal fixation system. 18 The results of this study showed that the incidence of empty shell signs in the study group was lower than that in the control group during follow-up (all ps < 0.05). This may be because the upper and lower vertebral body placement of fixed screws can reconstruct the height of the cone, consolidate the correction effect of internal fixation, and then reduce the occurrence of adverse reactions such as fracture and fall off of internal fixation.…”
Section: Recovery Timementioning
confidence: 56%
“…pointed out that percutaneous pedicle screw combined with injured screw can more effectively reconstruct spinal physiological sequences and maintain spinal stability 17 . Fei's research points out that minimally invasive percutaneous pedicle screw surgery could improve postoperative pain and surgical stress in patients with thoracolumbar fractures, which was beneficial for the recovery of injured vertebrae and the improvement of quality of life 18 . The results of the present study suggested that one universal screw placed percutaneously in the injured vertebral body, while fixed screws placed in the adjacent upper and lower vertebral bodies could significantly relieve the pain of patients with thoracolumbar fractures in the early postoperative period and reduce postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%